Fibroblast growth factor-23 and cardiovascular events in CKD - Scialla, Julia J; Xie, Huiliang; Rahman, Mahboob; Anderson, Amanda Hyre; Isakova, Tamara; Ojo, Akinlolu; Zhang, Xiaoming; Nessel, Lisa; Hamano, Takayuki; Grunwald, Juan E; Raj, Dominic S; Yang, Wei; et al. (Journal of the American Society of Nephrology, 2014)
An elevated level of fibroblast growth factor-23 (FGF-23) is the earliest abnormality of mineral metabolism in CKD. High FGF-23 levels promote left ventricular hypertrophy but not coronary artery calcification. We used survival analysis to determine whether elevated FGF-23 is associated with greater risk of adjudicated congestive heart failure (CHF) and atherosclerotic events (myocardial infarction, stroke, and peripheral vascular disease) in a prospective cohort of 3860 participants with CKD stages 2-4 (baseline estimated GFR [eGFR], 44±15 ml/min per 1.73 m(2)). During a median follow-up of 3.7 years, 360 participants were hospitalized for CHF (27 events/1000 person-years) and 287 had an atherosclerotic event (22 events/1000 person-years). After adjustment for demographic characteristics, kidney function, traditional cardiovascular risk factors, and medications, higher FGF-23 was independently associated with graded risk of CHF (hazard ratio [HR], 1.45 per doubling [95% confidence interval (CI), 1.28 to 1.65]; HR for highest versus lowest quartile, 2.98 [95% CI, 1.97 to 4.52]) and atherosclerotic events (HR per doubling, 1.24 [95% CI, 1.09 to 1.40]; HR for highest versus lowest quartile, 1.76 [95% CI, 1.20 to 2.59]). Elevated FGF-23 was associated more strongly with CHF than with atherosclerotic events (P=0.02), and uniformly was associated with greater risk of CHF events across subgroups stratified by eGFR, proteinuria, prior heart disease, diabetes, BP control, anemia, sodium intake, income, fat-free mass, left ventricular mass index, and ejection fraction. Thus, higher FGF-23 is independently associated with greater risk of cardiovascular events, particularly CHF, in patients with CKD stages 2-4.